Comparison of laminectomy and fusion vs laminoplasty in the treatment of multilevel cervical spondylotic myelopathy: A meta-analysis. Issue 13 (March 2019) - Yuan, Xiaojun; Wei, Chunmei; Xu, Wenhua; Gan, Xinrong; Cao, Shengsheng; Luo, Jiaquan
Abstract: Purpose: The purpose of this study is to evaluate the clinical safety and efficacy between laminectomy and fusion (LF) versus laminoplasty (LP) for the treatment of multi-level cervical spondylotic myelopathy (CSM). Methods: The authors searched electronic databases using PubMed, MEDLINE, Embase, Cochrane Controlled Trial Register, and Google Scholar for relevant studies that compared the clinical effectiveness of LF and LP for the treatment of patients with multilevel CSM. The following outcome measures were extracted: the Japanese Orthopaedic Association (JOA) scores, cervical curvature index (CCI), visual analog scale (VAS), Nurich grade, reoperation rate, complications, rate of nerve palsies. Newcastle Ottawa Quality Assessment Scale (NOQAS) was used to evaluate the quality of each study. Data analysis was conducted with RevMan 5.3. Results: A total of 14 studies were included in our meta-analysis. No significant difference was observed in terms of postoperative Japanese Orthopaedic Association score ( P  = .29), visual analog scale neck pain ( P  = .64), cervical curvature index ( P  = .24), Nurich grade ( P  = .16) and reoperation rate ( P  = .21) between LF and LP groups. Compared with LP group, the total complication rate (OR 2.60, 95% CI 1.85, 3.64, I 2  = 26%, P < .00001) and rate of nerve palsies (OR 3.18, 95% CI 1.66, 6.11, I 2  = 47%, P  = .0005) was higher in the LF group. Conclusions: Our meta-analysis reveals that surgical treatments of multilevel CSM are similar in terms of most clinical outcomes using LF and LP. However, LP was found to be superior than LF in terms of nerve palsy complications. This requires further validation and investigation in larger sample-size prospective and randomized studies.